2022
DOI: 10.1186/s10194-022-01409-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis identified novel susceptible genes of restless legs syndrome in migraineurs

Abstract: Background Restless legs syndrome is a highly prevalent comorbidity of migraine; however, its genetic contributions remain unclear. Objectives To identify the genetic variants of restless legs syndrome in migraineurs and to investigate their potential pathogenic roles. Methods We conducted a two-stage genome-wide association study (GWAS) to identify susceptible genes for restless legs syndrome in 1,647… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Genome editing has been used to model human tumors such as liver cancer [ 70 ], paraganglioma [ 71 ], skin melanoma [ 72 ], and epithelioid sarcoma [ 73 ]. Among neurologic diseases, amyotrophic lateral sclerosis [ 74 ], epilepsy [ 75 , 76 , 77 , 78 , 79 ], Hirschprung’s disease [ 80 ], autism [ 81 , 82 , 83 , 84 ], spastic paraplegia [ 85 ], restless legs syndrome [ 86 ], insomnia [ 87 ], microcephaly [ 46 ], neurotransmitter function of dopamine [ 88 ], monoamine [ 89 ], and others [ 90 , 91 ]. Cleft lip and cleft palate mutants also have been tested [ 92 ].…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%
“…Genome editing has been used to model human tumors such as liver cancer [ 70 ], paraganglioma [ 71 ], skin melanoma [ 72 ], and epithelioid sarcoma [ 73 ]. Among neurologic diseases, amyotrophic lateral sclerosis [ 74 ], epilepsy [ 75 , 76 , 77 , 78 , 79 ], Hirschprung’s disease [ 80 ], autism [ 81 , 82 , 83 , 84 ], spastic paraplegia [ 85 ], restless legs syndrome [ 86 ], insomnia [ 87 ], microcephaly [ 46 ], neurotransmitter function of dopamine [ 88 ], monoamine [ 89 ], and others [ 90 , 91 ]. Cleft lip and cleft palate mutants also have been tested [ 92 ].…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%
“…With regard to genetic studies of associations and correlations, several large studies based on the comparison of GWAS data have shown the existence of a shared genetic susceptibility between migraine and various disorders, including psychiatric disorders [ 140 , 141 ], ischemic stroke [ 142 ], coronary artery disease [ 143 ], hypertension [ 144 , 145 ], sleep disorders [ 146 ], and also endometriosis [ 147 ], fibromuscular dysplasia [ 148 ], type 2 diabetes, hyperlipidemia, autoimmune diseases, asthma, other respiratory conditions [ 144 ], restless legs syndrome [ 149 ] and hemostatic profile [ 150 ]. In contrast, one study found no causal link between genetic susceptibility to migraine and Alzheimer’s disease, intelligence, and brain size [ 151 ].…”
Section: Susceptibility Genes For Migraine With Aura and Migraine Wit...mentioning
confidence: 99%
“…Some reports appear to follow a non-Mendelian pattern of inheritance because, despite the apparent autosomal dominant mode of inheritance, the proportion of those affected (>50%) is higher than would be expected from typical autosomal dominant inheritance. Zimprich [ 3 ] proposed the possible role of genetic factors, trying to explain the characteristics of non-Mendelian inheritance patterns in RLS genetics and the existence of epigenetic inheritance in this disease family.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Many studies have attempted to identify the genes involved in the basic molecular mechanisms of this disease, but no single cause of RLS has been identified. [ 3 ] To date, genome-wide association studies of RLS have identified 13 different genes in several communities in Northern Europe, These genes are represented by chromosome 6p21.2 (BTBD9), 2p14 (MEIS1), 9p24.1-p23 (PTPRD), 15q23 (MAP2K5/SKOR1), and 16q12.1 (TOX3/BC034767) mononucleotides. [ 16 , 17 ] In addition, recent studies have identified 7 additional major susceptibility loci for RLS: RLS1 at 12q12-q21, RLS2 at 14q13-q21, RLS3 at 9p24-p22, RLS4 at 2q33, RLS5 at 20p13, RLS6 at 19p13, and RLS7 at 16p12.1.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation